2020
DOI: 10.1002/jum.15545
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Characterization of Pancreatic Tumors Using Contrast‐Enhanced Ultrasound and Shear Wave Elastography for Optimization of Surgical Strategies

Abstract: Objectives-To evaluate intraoperative contrast-enhanced ultrasound (IoCEUS) and intraoperative shear wave elastography (IoSWE) for characterization of focal pancreatic lesions (FPLs) in correlation with postoperative histologic results. Thereby, the impact of intraoperative ultrasound (US) on pancreas surgery was evaluated.Methods-Intraoperative CEUS and SWE data from 54 patients, who underwent pancreas surgery between 2017 and 2019, were analyzed retrospectively. Ultrasound examinations were performed with mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
0
6
0
1
Order By: Relevance
“…Previous studies reported good diagnostic performances of CEUS and SWE for intestinal, 46 thyroid, 47 and pancreatic 48 lesions. Some studies reported that the combined use of CEUS and micro‐flow imaging improved the diagnostic performance for breast tumors 49 .…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies reported good diagnostic performances of CEUS and SWE for intestinal, 46 thyroid, 47 and pancreatic 48 lesions. Some studies reported that the combined use of CEUS and micro‐flow imaging improved the diagnostic performance for breast tumors 49 .…”
Section: Discussionmentioning
confidence: 91%
“…[17,18] Despite the current controversial conclusions, auxiliary measures such as intraoperative ultrasonography are helpful and sometimes mandatory to explore the exact spatial relationship between the tumor and the duct before determining the type of surgery, especially in cases where the tumor-duct distance is small or indeterminate based on pre-operative imaging data. [19,20] In this case, a 49-year-old female patient was diagnosed with functional pancreatic insulinoma, with no special symptoms, manifestations, comorbidities and chronic conditions. Base on the preoperative imaging data, the tumor was benign was far away from the MPD (>3 cm) and a stent at the MPD was not placed.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 , 18 ] Despite the current controversial conclusions, auxiliary measures such as intraoperative ultrasonography are helpful and sometimes mandatory to explore the exact spatial relationship between the tumor and the duct before determining the type of surgery, especially in cases where the tumor-duct distance is small or indeterminate based on pre-operative imaging data. [ 19 , 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…Future studies involving HRUS could investigate facial muscles changes occurring postoperatively, as well as following conservative management. US applying 3D technology or a volumetric assessment may reveal intramuscular changes associated with different (non-)surgical procedures [ 66 ]. Further studies are needed to determine how US morphologic and functional findings, such as (facial) muscle size and dynamic muscular behavior, correlate with clinical conditions like muscular hypertonicity.…”
Section: Discussionmentioning
confidence: 99%